Drunken patients in the general hospital: their care and management. Issue 953 (4th March 2005) - Malone, D; Friedman, T
Abstract : In Britain alcohol consumption is increasing, 1 in 4 men and 1 in 10 women drink hazardously, 1 in 3 young men, and 1 in 4 young women regularly binge drink. Mortality rates attributable to alcohol have doubled; with 1 in 5 male inpatients having an alcohol related problem. The increasing problem of managing drunken behaviour in accident and emergency departments is discussed. Although an alcohol history is recommended for all admissions, because of various reasons, hazardous drinkers continue to miss the opportunity of effective interventions. In addition to the more formal treatments for alcohol problems, there is a wealth of evidence reporting the effectiveness of brief interventions carried out by a range of health professionals can lead to long term reductions in alcohol consumption. This review discusses practical and legal issues of the assessment, screening tools, and management of intoxicated patients.